Endoscopic criteria to evaluate tumor response of rectal cancer to neoadjuvant chemoradiotherapy using magnifying chromoendoscopy. Issue 8 (August 2018) - Chino, Akiko; Konishi, Tsuyoshi; Ogura, Atsushi; Kawachi, Hiroshi; Osumi, Hiroki; Yoshio, Toshiyuki; Kishihara, Teruhito; Ide, Daisuke; Saito, Shoichi; Igarashi, Masahiro; Akiyoshi, Takashi; Ueno, Masashi; et al.
Abstract: Background and aims: Precise endoscopic assessment of complete response to neoadjuvant chemoradiotherapy before surgery is important for optimizing surgical and non-surgical treatment. We prospectively evaluated the accuracy of the newly proposed endoscopic criteria to identify complete response, using magnifying chromoendoscopy. Methods: New endoscopic criteria were created to define endoscopic complete response, near complete response and incomplete response, using magnifying chromoendoscopy. The criteria contained notable endoscopic findings, including shape of the scar, state of the ulcer, finding of white moss, presence of residual protruded nodules, regenerated pits of the scar, presence of neoplastic pit patterns, and extension of rectal wall. Seventy-nine patients with rectal cancer who received neoadjuvant chemoradiotherapy were prospectively evaluated 1–3 days before resection. Diagnostic accuracy to identify pathological complete response and interobserver agreement among a supervising colonoscopist and two trainees were investigated. Results: Pathological complete response was obtained in 17 patients (21.5%). The diagnostic accuracy of endoscopic complete response was 85%, with a sensitivity of 47%, specificity of 97%, positive predictive value of 80% and negative predictive value of 77%. The kappa-value for interobserver agreement across 3 doctors was 0.57 (standard error, 0.74; 95% confidence interval, 0.39–0.76). Conclusion: The newly proposed endoscopic criteria using magnifying chromoendoscopy achieved excellent diagnostic accuracy to determine good responders to neoadjuvant chemoradiotherapy in rectal cancer, with fair interobserver agreement. The criteria could be clinically useful to select patients for non-surgical management.